The Impact of Online Gambling on Household Harmony in Bojonegoro Regency: Dampak Perjudian Online terhadap Kerukunan Rumah Tangga di Kabupaten Bojonegoro - Dadung Harjo Yudanto; Heru Ismaya (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Humans are social creatures. One of its manifestations is the formation of a marriage between a man and a woman in building a happy household as the smallest unit in society. The rise of online gambling in Bojonegoro Regency has an effect on the household. Ranging from financial losses, addiction, to emotional instability. This research uses a descriptive qualitative approach to analyze the impact of online gambling on household harmony. The qualitative method was chosen because it is able to describe the phenomenon holistically through narrative data), while the descriptive approach is used to portray actual conditions without manipulation of variables. Online gambling has a significant impact on household harmony which starts with a drastic deterioration in communication, When couples are entangled in online gambling activities, the time and attention that should be given to interact with the family is instead diverted to online games. So that daily communication becomes tense and conflict-prone. As a result, couples feel neglected, unappreciated, and have difficulty establishing a healthy discussion space